1986
DOI: 10.1017/s0043174500068004
|View full text |Cite
|
Sign up to set email alerts
|

Variation Within Pure Lines of Wild Oats (Avena fatua) in Relation to Degree of Primary Dormancy

Abstract: The germination of caryopses on water or GA3 solutions was used to characterize the degree of primary dormancy present in the seed progeny of 10 genetically pure lines of wild oats (Avena fatua L. # AVEFA). These 10 lines represented a range of types from lines exhibiting no dormancy to those with a high degree of dormancy. Repeated propagation of these pure lines under constant environmental conditions identified several genetically inherited characters that were associated with the inherited differences in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…Similarly, PoljakoffMayber et al (2002) observed that GA 3 did not affect the germination of dormant intact Avena sativa propagules although it did accelerate the germination of dissected dormant caryopses. It has been shown that GA 3 has a stimulatory effect on the germination of dormant Avena fatua caryopses (Adkins et al 1986;Fennimore and Foley 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, PoljakoffMayber et al (2002) observed that GA 3 did not affect the germination of dormant intact Avena sativa propagules although it did accelerate the germination of dissected dormant caryopses. It has been shown that GA 3 has a stimulatory effect on the germination of dormant Avena fatua caryopses (Adkins et al 1986;Fennimore and Foley 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Dormant seeds of Avena fatua L. (wild oat) do not germinate under conditions which normally favour germination (Fennimore and Foley 1998) although germination can be enhanced by gibberellin A 3 (GA 3 ) (Adkins et al 1986;Fennimore and Foley 1998), ethylene (Adkins and Ross 1981) or smoke extract (Adkins and Peters 2001). To date, knowledge about the role of smoke in the regulation of Avena fatua seeds is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Genetically pure dormant line M73 and nondormant line SH430 wild oat seeds (Avenafatua L.) were used [1]. M73 plants were grown in a greenhouse at constant temperature (20 + 3 ° C) and photoperiod (18 h light, 6 h dark).…”
Section: Plant Materialsmentioning
confidence: 99%
“…There is considerable genetic variability of germination behavior in the natural wild oat population (Naylor and Jana 1976;Adkins et al 1986). This genetic variability is evident, with respect to both the duration of primary dormancy and seed response to changing environmental factors, in genetic lines of this very persistent weed of temperate cereal crops (Simpson 1990).…”
Section: Introductionmentioning
confidence: 99%